GenerativeComponents software gives "bending the rules" awhole new meaning. - DS (Architectural Record)
Some architects can program computers, some programmers are architects—but having the one skill shouldn't mean having to have the other, says Robert Aish, computer aided design pioneer and director of Bentley Systems Inc. The new parametric design software he has developed, Generative Components is poised to allow to harness computing power for customized designs. Generative Components lets designers create rules for a project—for example, a complex stadium roof of known dimensions and curvature—and form specialized components to be used to construct it. These components then populate a design that's generated automatically according to the rule. If the rule changes—if the designer modifies the roof's span or curvature—so too do the shape, orientation, and behavior of all its component parts, much like changing a formula in a spreadsheet affects all the values on which that formula is based. It also differs significantly from parametric programs like Autodesk's Revit, whose chief benefit is production efficiency achieved by embedding non-design information like cost and manufacturer into well-understood building components like doors.